Sustainable Concrete Technology - Sim Jonsung; Lee K.H. (Institute of Research and Community Outreach - Petra Christian University, 2015)
The growing concern over global warming and significant ecological changes requires sustainable development in all fields of science and technology. Concrete not only consumes huge amount of energy and natural sources, but also emits large amount of CO2, mainly due to the production of cement. It is evident that such large amount of concrete production has put significant impact on the energy, resource, environment, and ecology of the society. Hence, how to develop the concrete technology in a sustainable way has become a significant issue. In this paper, some of Korean researches for sustainable development of concrete are presented. These are sustainable strengthening for deteriorated concrete structure, sustainable reinforcement of new concrete structure, sustainable concrete using recycled aggregate and supplementary cementing materials and finally application of each technique to precast concrete.